Association between vitamin B6 levels and rheumatoid arthritis: a two-sample Mendelian randomization study - Liu, Yanglin; Wang, Xukai; You, Min; Zheng, Meiling; Yu, Miao; Leng, Xiangyang (Frontiers in Nutrition, 2024)
Background Micronutrients play a crucial role in rheumatoid arthritis (RA). Changes in micronutrient levels in RA patients can lead to the worsening of their condition. Though significant correlations between RA and micronutrients have been found in earlier observational studies, their underlying causal relationship is still unknown. This study aimed to elucidate the causal genetic relationships between 15 micronutrients (copper, zinc, magnesium, vitamins A, C, E, D, B6, B12, folate, carotene, iron, selenium, calcium, potassium) and RA. Method The exposure factors and outcome data used in the two-sample Mendelian randomization (MR) were derived from publicly available summary statistics data of European populations. The GWAS data for exposure factors were obtained from the OpenGWAS database. For the outcome data of RA, we utilized data from the FinnGen database. We used the MR principle to remove confounding factors and conducted MR analyses using five methods: inverse variance weighted (IVW), MR Egger, weighted median, simple mode, and weighted mode, with IVW as the primary method. Then, we identified micronutrients related to RA and performed MR analyses on these elements, including heterogeneity analysis and pleiotropy analysis such as MR-Egger intercept, MR-PRESSO method, and “leave-one-out” analysis. Finally, we conducted multivariable MR analyses and performed sensitivity analyses again. Results The IVW analysis revealed a relationship between vitamin B6 and RA (p: 0.029, OR: 1.766, and 95% CI: 1.062–2.938). Sensitivity analysis confirmed the validity and reliability of this result. Conclusion This study revealed a causal relationship between vitamin B6 and RA, with vitamin B6 being identified as a risk factor for RA. This finding could contribute to the diagnosis and supplementary treatment of RA patients, providing a reference for subsequent basic research and developing new drugs.